Interruptions of nursing activities: contributions to patient and professional safety. - Monteiro, Cintia; Ariane Ferreira Machado Avelar; Mavilde Luz Gonçalves Pedreira (Acta Paulista de Enfermagem, 2020)
Objective: To classify activities performed by nurses, to identify interruptions and to verify human and environmental factors associated with interruptions. Methods: Observational study conducted with a sample comprising 25 nurses working in pediatric or adult, surgical or intensive care units of a university hospital. Results: We observed 2,295 activities, most of them were classified as indirect patient care (38.6%) and direct patient care (22.5%). Seven hundred and nineteen (31.3%) interrupted activities were identified, with mean of 1.6 interruptions in the same activity, thus totaling 1,180 interruptions. There was greater number of interruptions during the indirect care (44.7%), and their main sources were the nursing (43.3%), and the physicians and residents (16.5%) staffs. The number of individuals in the units (staff and family/visitors), the proportion of patients under high-dependency, the number of healthcare and allied professionals influenced the number of interruptions. Conclusion: There were interruptions in all types of activities performed by the nurses, even in those characterized as bedside interventions, which can jeopardize patient safety.